A Philosophical Search for Happiness: An Enigma or Reality? (Philosophy and Progress, 2023)
In philosophy happiness occupies a dominant position. From the beginning of philosophy, we find the scholarly engagement of philosophers in search of happiness for human being. It is actually a perennial search of mankind throughout history. My attempt in this paper is to become a part of that august journey. I will try to focus some points in my paper. At first, I will try to give an analytic presentation about the nature of happiness with references to different philosophers and philosophical schools. In this part I will attempt to find out the root causes of the changing patterns of happiness by maintaining a chronological order. In the next part I will try to depict some significant debates regarding the pursuit of happiness. The question of enigma and reality will be dealt here in a comparative fashion. And finally, I will try to give some recommendations and suggestions for a happy life.As this is a qualitative work, here I confine myself within some relevant textbooks of philosophy and recent research articles on the pursuit of happiness. Content analysis, comparative discussion with a critical outlook and philosophical speculation will be within the research methodology of the paper.Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 129-151